SpongeBob SquarePants. The complete first season [videorecording (DVD)] - Hillenburg, Stephen (2003)
First season of the character-driven cartoon chronicling the nautical and sometimes nonsensical adventures of SpongeBob, an incurably optimistic and earnest sea sponge, and his undersea friends.